Peningkatan Kemampuan Menulis Teks Eksposisi Melalui Penerapan Strategi Gallery Walk Kelas XI SMK Al-Madaniyah Pamekasan - Naulia Fadilah; Kusyairi Kusyairi (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aimed to improve the expository text writing skills of eleventh-grade students at SMK Al-Madaniah Pamekasan through the implementation of the Gallery Walk strategy. This research employed Classroom Action Research (CAR) conducted in two cycles. Each cycle consisted of planning, action, observation, and reflection stages. The subjects of this study were 17 eleventh-grade students of SMK Al-Madaniah Pamekasan. Data were collected through tests, observations, and questionnaires. The data were analyzed using descriptive quantitative analysis. The results showed that the implementation of the Gallery Walk strategy improved students' expository text writing skills. In Cycle I, the average score was 64.70 with a learning mastery percentage of 29.41%. In Cycle II, the average score increased to 83.47 with a learning mastery percentage of 93.75%. Students' learning activities also increased from 65% in Cycle I to 95% in Cycle II. In addition, students showed positive responses toward the implementation of the Gallery Walk strategy. Therefore, the Gallery Walk strategy proved to be effective in improving the expository text writing skills of eleventh-grade students at SMK Al-Madaniah Pamekasan.